Online Learning Phenomenon: From the Perspective of Learning Facilities, Curriculum, and Character of Elementary School Students - Abdurrahmansyah Abdurrahmansyah; Hamdan Sugilar; Ismail Ismail; Dewi Warna (MDPI AG, 2022)
This article aimed to describe the online learning phenomenon from the perspective of learning facilities, curriculum, and students' characters in schools and the correlation among those three variables. This research employed a qualitative descriptive method. The data were collected through interviews, observations, and questionnaires. The research subject was the fifth-grade class of an elementary school in Palembang, which consisted of 19 students' parents, 8 teachers, and 47 students. The findings showed that almost half of the total number of students experienced limitations in online learning facilities, most elementary school teachers could not develop curriculum and online learning models, and the online learning phenomenon triggered a decline in the students' characters.